MODEL PELAYANAN KESEHATAN BERBASIS PARTISIPASI MASYARAKAT UNTUK MENINGKATKAN PELAYANAN KESEHATAN JIWA PADA MASYARAKAT SETEMPAT - Abi Muhlisin; Arum Pratiwi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Community-Based Participatory research is very important, because this study is the needs of local community that is facilitated by the researchers to bridge the gap between knowledge and practice of health and improve public health conditions through community involvement and social action. In this study, the local community has a significant mental health problem, then I trained community as mental health workers included how to take care of suffering from mental illness people in community life. The purpose of this research is to increase mental health workers (cadres) knowledge periodically through training and mental health care practices that were assisted by a team of researchers. The number of participants in the beginning of the study 30 people then selected 10 people who have the best value and the most skilled. Analysis of the level of knowledge and skills of cadres periodically used repeated measure ANOVA.The results of the study showed that (1) differences mental health worker knowledge of each period significantly by the results of tests of between-subjects effects 189.476 with a P value of .00 (2) The level of knowledge of the most effective after they were given skill training with Wilk lambda value of 248.71 by P value 0.00. Thus, it can be concluded the repetition of skills training impact to the level of knowledge of mental health workers. This program is recommended for the sustainability of the health department's involvement in funding and as a strategic conduction audience.Keywords: community participation, mental health workers knowledge, community mental health services.